A, The Darurat Normalisasi Cyber Sexual Harassment terhadap Perempuan di Media Sosial Instagram Era Digital: Bentuk- Bentuk Cyber Sexual Harrasment Yang Terjadi di Media Sosial Instagram - Sitohang, Dita Permatasari; Fatmariza; Maria Montessori; Rinia Zatalini (Global Action and Education for Society, 2025)
This research is based on the problem hof rapid technological developments that are changing people's interaction patterns on social media. Even though it provides many benefits, social media is often misused for cyber sexual harassment, especially against women. This research aims to map forms of cyber sexual harassment on the social media Instagram which views women as objects of sexuality. This research uses a qualitative approach with content analysis methods. Data was collected from four female figure public Instagram accounts, namely the initials NM, GA, RK, and AH. These accounts included 14 posts with a total of 209 comments containing harassment, consisting of 180 real accounts and 29 fake accounts. Data collection techniques were carried out through documentation studies and data scraping, which were then analyzed using coding techniques for distribution mapping with the help of Atlas.ti software. The validity of the data was tested through triangulation methods and content observation to ensure the validity and reliability of the findings. The research results show that there are six forms of cyber sexual harassment that occur on Instagram social media, namely: (1) victim blamming, (2) spamming, (3) sexting, (4) body shaming, (5) flaming, and (6) religious-based harassment.